Effect of judo practice on changes in urinary substances and blood hormones - Ozawa, Y.; Ogi, K.; Ogasawara, M.; Hamada, H.; Mesaki, N. (Advances in Exercise and Sports Physiology, 2005)
This study investigated the effects of judo practice on changes in urinary volume, areatinine (Creat), sodium ion (Na+) and blood aldosterone (Aldo), atrial natriuretic peptide (ANP), Creat and lactic acid. Seven healthy university male judo wrestlers performed two typical judo practices, 5 minutes free sparring in standing position (Randori: Rand) and 5 minutes repetitive shoulder throw (Uchikomi: Uchi) with their maximal effort, and warming-up exercise(Control: Cont). Urine was collected 4 times in a row according to the following schedule for each types of exercise: (1) after 30 minutes rest in a sitting position following urination, (2) after 30 minutes warming-up exercise, (3) after 30 minutes of recovery from exercise and (4) after 60 minutes of recovery from exercise. Blood sample was collected twice: during the resting period and at 10 minutes after exercise. The urine taken 30 minutes after the end of exercise, which was considered to most distinctively show the effect of practice, was compared between Rand and Uchi. Urinary volume and Na+ were significantky higher for Uchi, while urinary Creat concentration was significantly lower for Uchi. No significant difference was observed in post-exercise creatinine clearance (Cer) between Rand and Uchi. Post-exercise blood concentrations of Aldo and ANP significantly increased from pre-exercise levels both for Rand and Uchi. Post-exercise blood concentrations of lactic acid were significantly higer for Uchi and Rand. Thus urinary excretion after Uchi, in particular, showed a specific change. The possible reason was that Uchi was accompanied by heavy lactie aced oxygen debt that might have depressed the function of kidney tubule, resulting in loss of reabsorptive function in response to glomerular filtration rate.